2020
DOI: 10.1016/j.ssmph.2020.100698
|View full text |Cite
|
Sign up to set email alerts
|

Rising inequality of infant health in the U.S.

Abstract: Has infant health inequality narrowed or grown in recent decades? Inequality may have narrowed due to expanded medical insurance coverage and greater knowledge about fetal health. However, greater income inequality may have reduced health for births to the most economically disadvantaged mothers, leading to growing infant health inequality. We use administrative birth certificate data for over 22 million births to examine trends in inequality of infant health from 1989 to 2018 in the U.S. This period allows us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In terms of trends in infant health, research from Chile has shown that the gestational age and birth weight of live births have significantly changed over the past decades (Abufhele, Pesando, and Castro 2022;Lopez and Bréart 2012;Torche and Abufhele 2021). Despite the rapid economic growth that the country experienced over the last decades, the share of children born with less than 2,500 g-the definition of low weight at birth-and the share of children born before 37 weeks of gestation-the definition of preterm birth-have increased over time, echoing recent worrisome evidence from the United States (Rauscher and Rangel 2020). In 1990, the proportion of LBW was 5.7 percent, while this rose to 6.3 percent in 2015.…”
Section: Fertility and Covid-19 In The Chilean Contextmentioning
confidence: 99%
“…In terms of trends in infant health, research from Chile has shown that the gestational age and birth weight of live births have significantly changed over the past decades (Abufhele, Pesando, and Castro 2022;Lopez and Bréart 2012;Torche and Abufhele 2021). Despite the rapid economic growth that the country experienced over the last decades, the share of children born with less than 2,500 g-the definition of low weight at birth-and the share of children born before 37 weeks of gestation-the definition of preterm birth-have increased over time, echoing recent worrisome evidence from the United States (Rauscher and Rangel 2020). In 1990, the proportion of LBW was 5.7 percent, while this rose to 6.3 percent in 2015.…”
Section: Fertility and Covid-19 In The Chilean Contextmentioning
confidence: 99%
“…From a methodological standpoint, we begin by providing graphical descriptive evidence of the relationship between mobile-phone ownership and whether the child is considered a LBW infant. The cut-off selected for low-weight births is when a child weighs 2,500 grams or less [28][29][30][31], a variable which was created from the original continuous one, also kept as a separate independent outcome-as continuous and dichotomous outcomes may retain different amounts of information. As far as the outcomes are concerned, three observations are worth of note.…”
Section: Plos Onementioning
confidence: 99%
“…A systematic review of the literature through the end of 2017 found that Medicaid expansion “was associated with increases in coverage, service use, quality of care, and Medicaid spending” (Mazurenko et al, 2018). One study found that the law's expansion of access to health care contributed to a reduction in infant health inequality (Rauscher & Rangel, 2020). Another found that, by the end of 2018, states that had expanded Medicaid experienced significantly fewer premature cancer deaths than states that had not expanded Medicaid.…”
Section: The Aca and The Goal Of Reducing Health Care Inequalitiesmentioning
confidence: 99%